European sorghum from field to functional food: Nutritional composition, bioactive compounds, and processing-induced biotransformation - Jakub Frankowski; Mateusz Labudda; Muhammad Salman Farid; Anna Przybylska-Balcerek; Katarzyna Szambelan; Maciej Ireneusz Kluz; Przemysław Łukasz Kowalczewski; Miroslava Kačániová; Łukasz Łopusiewicz (Food Bioscience, 2026)

Can biological control involving predatory mites mitigate plant stress caused by phytophagous mites? - Wesley Borges Wurlitzer; Julia Renata Schneider; Mateusz Labudda; Julia Huppes Majolo; Marcelo Lattarulo Campos; Joaquim A. G. Silveira; Daniel Guimarães Silva Paulo; Maria Goreti de Almeida Oliveira; Noeli Juarez Ferla (Planta, 2026)
Main conclusion The biological control of phytophagous mites mediated by predatory mites promotes the maintenance of plant physiology by mitigating damage and preserving key traits related to photosynthesis and development. Abstract The immune system of plants, upon perceiving the presence of phytophagous mites, triggers signals mediated by reactive oxygen species (ROS). Under intense infestations, these redox signals can trigger oxidative stress, which compromises vital characteristics related to plant fitness. The use of pesticides as a management strategy is increasingly limited by resistance and collateral physiological impacts on plants. The release of predatory mites has emerged as an effective and sustainable biological approach. Predator-mediated foraging may suppress phytophagous mite infestations and mitigate the physiological stress of plants by limiting metabolic expenditures and physiological disturbances related to photosynthesis, growth, and reproduction. Thus, we review the benefits and risks of signals mediated by ROS in plants under attack by phytophagous mites. We conceptualize a stress state for plants under attack by these organisms and describe the benefits of foraging predatory mites reported in the literature from a meta-analytical perspective. Based on existing studies, we show that these natural enemies mitigate damage and the intensification of foliar chlorosis, limiting impacts on leaf area, the number of leaves, and the size of the plants. Furthermore, we speculate how the intensity of stress in the plant could act as a key point in the signals emitted to attract predatory mites. Finally, we emphasize the urgency of integrating this new perspective into future studies to improve the evaluation of the efficiency of natural enemies to benefit plant performance.

Salt stress and the wheat curl mite (Aceria tosichella) infestation reprograms barley nitrogen metabolism via nitric oxide signaling - Jakub Graska; Justyna Fidler-Jarkowska; Ewa Muszyńska; Marta Gietler; Małgorzata Nykiel; Beata Prabucka; Mariusz Lewandowski; Mateusz Labudda (Planta, 2026)

The effects of soil salinity and wheat curl mite infestation on the antioxidative response of barley - Jakub Graska; Justyna Fidler; Marta Gietler; Małgorzata Nykiel; Beata Prabucka; Mariusz Lewandowski; Mateusz Labudda (Plant and Soil, 2025)
Background and Aims Climate changes profoundly influence the level of stress that plants experience. This study was conducted to investigate the redox homeostasis of barley in response to salinity, infestation by Aceria tosichella Keifer. (the wheat curl mite, WCM), and the combined effects of these stress factors. Methods Hordeum vulgare L. plants were treated with sodium chloride at concentrations of 50 mM and 100 mM and were inoculated with WCM. The plants were also exposed to both stressors simultaneously. Biochemical and molecular parameters were measured to evaluate the potential role of reactive oxygen species (ROS) in modulating barley’s response. Results The analysis of ROS and antioxidant levels revealed distinct patterns based on specific stress factors. Hydrogen peroxide levels increased in all treatments, indicating a plant redox imbalance. In contrast, superoxide anion levels rose only with WCM infestation, suggesting a specific response to this pest. Lipid peroxidation decreased with WCM inoculated combinations. Conversely, carbonyl group content increased with NaCl and combined stresses but declined with WCM. Variations in ascorbic acid to dehydroascorbic acid and reduced to oxidized glutathione ratios suggest complex regulation of antioxidant metabolism. Moreover, significant changes in the activities and gene expression of key enzymes, including catalases, peroxidases, and superoxide dismutases, highlight the critical role of antioxidant mechanisms in plant responses to stress. Conclusion Our research results indicate that the response of barley to a combination of stress factors, such as salinity and WCM, differs significantly from the responses induced by their single exposure.

Application of silver and selenium nanoparticles to enhance plant-defense response against biotic stressors - Anielkis Batista; Van Chung Mai; Katarzyna Sadowska; Mateusz Labudda; Philippe Jeandet; Iwona Morkunas (Acta Physiologiae Plantarum, 2025)
The present review discusses the role of silver (AgNPs) and selenium (SeNPs) nanoparticles at different concentrations in the regulation of plant defence responses to the biotic stressors. Study of the role of the above nanoparticles (NPs) has generated considerable interest because these caused significant changes in the framework of plant growth and their metabolism and play an important role in responses to biotic stress factors. Numerous results of metabolomics studies provide evidence that NPs change the profile of metabolites and their concentrations. NPs were applied as potential tools to improve the growth of plants, plant tolerance to abiotic stresses and food production, but research on the environmental safety of their use in agriculture is still necessary. The response of plants to the application of NPs depends on their concentration, plant species, exposure time and stage of development.

Tetranychus ludeni (Acari: Tetranychidae) infestation triggers a spatiotemporal redox response dependent on soybean genotypes - Wesley Borges Wurlitzer; Julia Renata Schneider; Joaquim A. G. Silveira; Maria Goreti de Almeida Oliveira; Mateusz Labudda; Geraldo Chavarria; Ani Caroline Weber; Lucélia Hoehne; Gizele Martins Pinheiro; Naiara Nunes Vinhas; Luana Fabrina Rodighero; Noeli Juarez Ferla (Planta, 2024)

Reactive oxygen species metabolism and photosynthetic performance in leaves of Hordeum vulgare plants co-infested with Heterodera filipjevi and Aceria tosichella - Mateusz Labudda; Krzysztof Tokarz; Barbara Tokarz; Ewa Muszyńska; Marta Gietler; Mirosława Górecka; Elżbieta Różańska; Anna Rybarczyk-Płońska; Justyna Fidler; Beata Prabucka; Abdelfattah A. Dababat; Mariusz Lewandowski (Plant Cell Reports, 2020)
Key message Defence responses of cyst nematode and/or wheat curl mite infested barley engage the altered reactive oxygen species production, antioxidant machinery, carbon dioxide assimilation and photosynthesis efficiency. Abstract The primary aim of this study was to determine how barley responds to two pests infesting separately or at once; thus barley was inoculated with Heterodera filipjevi (Madzhidov) Stelter (cereal cyst nematode; CCN) and Aceria tosichella Keifer (wheat curl mite; WCM). To verify hypothesis about the involvement of redox metabolism and photosynthesis in barley defence responses, biochemical, photosynthesis efficiency and chlorophyll a fluorescence measurements as well as transmission electron microscopy were implemented. Inoculation with WCM (apart from or with CCN) brought about a significant suppression in the efficiency of electron transport outside photosystem II reaction centres. This limitation was an effect of diminished pool of rapidly reducing plastoquinone and decreased total electron carriers. Infestation with WCM (apart from or with CCN) also significantly restricted the electron transport on the photosystem I acceptor side, therefore produced reactive oxygen species oxidized lipids in cells of WCM and double infested plants and proteins in cells of WCM-infested plants. The level of hydrogen peroxide was significantly decreased in double infested plants because of glutathione–ascorbate cycle involvement. The inhibition of nitrosoglutathione reductase promoted the accumulation of S -nitrosoglutathione increasing antioxidant capacity in cells of double infested plants. Moreover, enhanced arginase activity in WCM-infested plants could stimulate synthesis of polyamines participating in plant antioxidant response. Infestation with WCM (apart from or with CCN) significantly reduced the efficiency of carbon dioxide assimilation by barley leaves, whereas infection only with CCN expanded photosynthesis efficiency. These were accompanied with the ultrastructural changes in chloroplasts during CCN and WCM infestation.

Efficient antioxidant defence systems of spring barley in response to stress induced jointly by the cyst nematode parasitism and cadmium exposure - Mateusz Labudda; Ewa Muszyńska; Marta Gietler; Elżbieta Różańska; Anna Rybarczyk-Płońska; Justyna Fidler; Beata Prabucka; Abdelfattah A. Dababat (Plant and Soil, 2020)
Aims This research aimed to establish how Hordeum vulgare responds to abiotic and biotic stress affecting in tandem. Methods Plants were inoculated with Heterodera filipjevi and treated with cadmium (Cd) concentration (5 μM) that can occur in the cultivated soil. To verify the hypothesis about participation of increased antioxidative defence in H. vulgare under stress, biochemical and microscopic methods were implemented. Results The amount of superoxide anions and hydrogen peroxide was diminished in plants that were both nematode-inoculated and cadmium-treated. Superoxide anions were rendered harmless by increased activity of superoxide dismutase, and H 2 O 2 was scavenged via Foyer-Halliwell-Asada pathway. The unique enhanced antioxidant capacity of double stressed plants was also linked with the accumulation of S -nitrosoglutathione as nitrosoglutathione reductase activity was inhibited. Furthermore, stimulated activity of arginase in these plants could promote polyamine synthesis and indirectly enhance non-enzymatic antioxidant mechanism. Results indicate that different antioxidants operating together significantly restricted oxidation of lipids and proteins, thus the integrity of cell membranes and protein functions were maintained. Conclusions The ROS deactivation machinery in barley leaves showed an unusual response during stress induced by H . filipjevi infection and cadmium treatment. Plants could induce a multi-component model of stress response, to detoxify Cd ions and efficiently repair stress damage.

Evaluation of heavy metal-induced responses in Silene vulgaris ecotypes - Ewa Muszyńska; Mateusz Labudda; Iwona Kamińska; Mirosława Górecka; Magdalena Bederska-Błaszczyk (Protoplasma, 2019)

Structural, physiological and genetic diversification of Silene vulgaris ecotypes from heavy metal-contaminated areas and their synchronous in vitro cultivation - Ewa Muszyńska; Mateusz Labudda; Elżbieta Różańska; Ewa Hanus-Fajerska; Anna Koszelnik-Leszek (Planta, 2019)